2012
DOI: 10.1016/j.theriogenology.2011.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Morphometrically-distinct sperm subpopulations defined by a multistep statistical procedure in Ram ejaculates: intra- and interindividual variation

Abstract: The existence of sperm subpopulations within the mammalian ejaculate has now been widely recognized. However, to the best of our knowledge, no data exist regarding the existence of sperm morphometric subpopulations within the ovine ejaculate. Computer assisted sperm morphometry analysis (ASMA) data and clustering methods were used in this study to identify sperm-head subpopulations in ram semen. Two experiments were carried out. In Experiment 1, ejaculates from 226 mature rams of the Manchega breed belonging t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 41 publications
1
26
0
2
Order By: Relevance
“…Marked phenotypic variation across sperm cells within a single ejaculate is ubiquitous, both in terms of sperm morphology [6][7][8] and performance [9]. However, sperm are generally considered products of the diploid paternal genome with no endogenous haploid gene expression, and sperm phenotype is thus thought not to reflect the haploid genome they carry [10].…”
Section: Introductionmentioning
confidence: 99%
“…Marked phenotypic variation across sperm cells within a single ejaculate is ubiquitous, both in terms of sperm morphology [6][7][8] and performance [9]. However, sperm are generally considered products of the diploid paternal genome with no endogenous haploid gene expression, and sperm phenotype is thus thought not to reflect the haploid genome they carry [10].…”
Section: Introductionmentioning
confidence: 99%
“…Using these methods, the existence of sperm-head morphometric subpopulations has been identified in different mammalian species (Gravance et al, 1996;Thurston et al, 1999;Rubio-Guillen et al, 2007;Alvarez et al, 2008;Esteso et al, 2009;de Paz et al, 2011;Marti et al, 2011b;Maroto-Morales et al, 2012). In a recent study (Vicente-Fiel et al, 2013b), the combination of CASMA-F technology with multivariate cluster analyses allowed the study of morphometric sperm subpopulations in four species of domestic artiodactyls (cattle, goat, sheep and pigs).…”
Section: Analysis Of Morphometric Resultsmentioning
confidence: 99%
“…Between these extremes, species such as bovine and porcine show an intermediate shape variability (Vicente-Fiel et al, 2013a,b). Size and shape sperm heterogeneity may be studied simultaneously using multivariate cluster Rubio-Guillen et al, 2007;Maroto-Morales et al, 2012;Vicente-Fiel et al, 2013b) and discriminant (Buendia et al, 2002;Hidalgo et al, 2008;Soler et al, 2014c) analysis.…”
Section: Results Of Sperm Morphometry In Different Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the literature on sperm head morphometry among different species is focused on semen processing effects, including the effects of cryopreservation and smear preparation techniques previous to morphometric analyses ; Esteso et al, 2003;Gravance et al, 2008). Only a few studies conducted in rams, however, have examined the effects of other environmental influences as the season effect, associated with photoperiod (Martí et al, 2012), the herd of origin (Maroto- Morales et al, 2012), or the age of the male, related with the sexual maturity (Martí et al, 2011), suggesting that these effects could explain an important part of the observed variation in sperm head morphometry, both in fresh (Maroto-Morales et al, 2012) and after cryopreservation process (Martí et al, 2011 and2012). Regarding to the age of the male, Martí et al (2011) showed that except for L all morphometric dimensions (A, P, W) values decreased with the increase of male age.…”
Section: Resultsmentioning
confidence: 99%